Model following methods in flight control systems - Tamkaya, Kadir (My University, 2020)
Probably the most important part during a flight is the landing phase because most of the accidents occur in this phase. Automatic Landing System (ALS) takes over control during this phase to avoid potential pilot-induced risks. However, some external disturbances, such as the windshear and turbulence, can jeopardize the safe landing. In this study, the final approach phase and flare phase are handled differently. A combination of some useful design methods is brought together to improve the performance of the conventional ALS even under severe weather conditions. The model following method is merged with the H∞ synthesis method to find out the optimal solution for a given cost function. The resultant H∞ optimal control problem is solved using Linear Matrix Inequalities (LMIs), and then a dynamic controller is constructed. The overall system is transformed into a P-K configuration, which is a highly compact control system structure. Thus, any disturbance or uncertainties can be included in the system explicitly. While the model following method continuously corrects the error, the H∞ controller attenuates any disturbance in the system. In addition to that, the robustness takes a vital role in the flight systems and needs to be handled correctly. Therefore, the windshear and turbulence models are considered as the disturbance, and their effects are minimized, such a way that the tracking performance remains unaffected. Thus, highly significant results are obtained using the proposed method even under severe weather conditions.
Tez (Doktora) - Yıldız Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2020
Keywords: Aircraft landing; ALS; H∞ synthesis; Model following control; Linear; Matrix inequlity